KOMPETENSI PROFESIONAL GURU DALAM MATA PELAJARAN SEJARAH KELAS VII MTsN LANGSAT KADAP RAO KABUPATEN PASAMAN - Putra, Andra Eka (Pendidikan Sejarah, 2014)
In conducting this research study about the professional competence of teachersin the subjects ofhistory class VIIMTsN Langsat Kadap Rao Pasaman West Sumatra Province. Professional competence of the teacherleads tothe ability ofa teacherin the subjectsof historyin MTsN Langsat Kadap Pasaman Rao. The purpose of this study was to reveal ordescribe the ability of an integrated social studies teachers in teaching history and how to educate child tostudy harderin MTsN Langsat Kadap Pasaman Rao. This research uses aqualitative approach and descriptive. This research was conductedby means of interviews and observations with the principal, teachers and a students Langsat Kadap Pasaman Rao. In conducting this study should bringthe equipment used to conduct qualitative research such as books, pens, camera. Results of the studyis to conduct research observations and interviews with principals, teachers and student swith the material the arrival of Islam in Indonesia, which has been taught to these students, in conducting this researchto geta very good result for teachers who teach in MTsN Langsat Kadap Rao shas the ability and insightin presenting the material to students and learning materials have been successfully menyampaiakn well and educate students as well instructional materials master, give good examples to the students as well ashow to deliver the learning materials and reamatis sequentially. Therefore teachers who teach inthis Kadat Langsat MTsN. Based on these resultsit can be concludedthat the professional competence of teachersis very importantin the world of science education, itshould be a professional teacher in teaching and learning in schools and within the community.